The Promotion of Knowledge and Attitude towards the Prevention of COVID-19 for Undergraduate Students - Kuantean Wongchantra,; Prayoon Wongchantra,; Suparat Ongon,; Likhit Junkaew,; Kannika Sookngam,; Uraiwan Praimee,; Surasak Kaeongam,; Thongchai Pronyusri,; Phanadda Ritsumdaeng, (Journal of Educational Issues, 2024)
The purpose of this research were to study and compare knowledge and attitudes towards prevention of COVID-19 before and after promotion and study and compare knowledge and attitudes towards the prevention of COVID-19 of students with different genders. The sample used in the study were 50 the third year undergraduate students in Environmental Education program, Faculty of Environment and Resource Studies, Mahasarakham University, which was derived by purposive sampling. The research tools were the coronavirus disease 2019 prevention and control manual for citizens by the Ministry of Health, knowledge test about prevention of COVID-19, attitude test towards prevention of COVID-19. The statistics used for data analysis were frequency, percentage, mean, standard deviation and hypothesis testing using Paired t-test and One-Way ANOVA. The results of the research showed that the posttest, the students had average scores of the knowledge and attitude towards prevention of COVID-19 higher than the pretest statistical significance (p < .05). And there was no significant difference of score of knowledge and attitude towards prevention of COVID-19 of students with different genders (p > .05).